THE EFFECT OF TILLAGE SYSTEM AND HERBICIDE ON LOSSES OF NUTRIENT AND ORGANIC MATTERS DUE TO EROSION IN LABORATORY OF LAPANG TERPADU FACULTY OF AGRICULTURE UNIVERSITY OF LAMPUNG - Burhannudin, Burhannudin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Land degradation is a serious problemwhich can reduce the land fertility and productivity. Themain cause of thedegradation is due to erosion phenomenon. It causes the fertile top soil losses which is good for plant growth.Tillage farming is particularly convinced as the prime cause on soil erosion. This research aims to determiningthe effect of tillage systemand herbicide to predict the losses of nutrients and organicmatter due to erosion. Thisexperiment was conducted at the Laboratory of Lapang Terpadu and Laboratory of Soil Science, Faculty ofAgriculture, University ofLampung inMay toAugust 2014. The experimentwas design as a factorial in completelyrandomized block design (RCBD) consisting of two factors, namely the tillage systemand herbicidewith 4 (four)repetitions. The results showed that the treatment of soil tillage, herbicides, and the combination of themdid notsignificantly affect the concentration ofN (total), K (exchangable), Ca (exchangable),Mg (exchangable), and theC (organic)matter in sediment.While theP (available), only the tillage systems that provided significant effect. Ata minimum tillage system P (available) concentration was significantly higher than the conventional tillagesystem. This was due to the nature of the immobil phosphorus, itmean the phosphorus in the soil remains in thetop soil otherwisemechanically inserted into the sub soil. The limited tillage onminimumtillage systems causesphosphorus remain inthe top soil, so thatwhen erosion occurs phosphorus losses inminimumtillage system willbe higher thanin conventional tillage. The conventional tillage systemcauses loss of P (available) of 0,016 kg/haand the minimumtillage systemcauses loss of P (available) of 0,01 kg/ha.